Analisa Penyebab Penurunan Badan Jalan Di Ruas Jalan Baru Furia Kotaraja STA (0+000 – 0+520) - Alfian Adie Chandra; Ira Widyastuti; Maurids Thomas Sapari (Jurnal Sipil Terapan, 2023)
Topography in Papua is generally an area consisting of mountains and valleys that have various slopes. Means of transportation was planned in such a way that it had to go through the slope. One of them is on the New Furia Kotaraja road section. On this road section, the slope is cut so that the road is made safe and comfortable for motorists to pass. However, at several points there was damage to the road body which was identified as a landslide, namely the formation of an avalanche crown on the surface of the road body. Therefore it is necessary to analyze the stability of the slopes in order to obtain ways to overcome them. Analysis of slope stability on the New Furia Kotaraja road section used the GeoStudio 2007 Slope/W assist program and manually used the Fellenius method. From the analysis that has been carried out, given the condition of the road load and pore water pressure, it can be concluded that the slopes on the New Furia Kotaraja road section Km 0+000 – 0+520 are unstable slopes because according to the results of the calculation of the slope safety factor based on the Fellenius formula, namely 0.589, according to Bowles, the slope is unstable if the factor of safety is less than 1.07. Thus, the slopes on the Baru Furia Kotaraja Km 0+520 road section need to be treated in the form of a box cover / culvert, with a surface depth of 280 cm box coler because at that depth it has a rather dense soil type, silty sand, and a channel is also planned. square type drainage with dimensions (b = 2.00 ; h = 1.70 m ) to drain water discharge (Q = 0.68 m3/s), the slope becomes stable because the slope safety factor changes to 1.259 which according to Bowles's opinion the slope is included stable when the factor of safety is above 1.25.